PP.11 One Third of Non-Anomalous Term Stillbirths Are Associated with Abnormal Fetal Growth. (26th April 2013) - Moraitis, AA; Smith, GC
Abstract : Background: Approximately one third of all stillbirths occur at term. These losses are potentially preventable by early delivery at 37 weeks. One means of screening to detect babies at risk of term stillbirth would be to use ultrasound to assess abnormalities of fetal growth. However, there is limited information on the importance of fetal growth in determining the risk of stillbirth at term. Methods/Results: We studied registries of Scottish maternity and stillbirth data and identified 668, 887 eligible records of term births since 1992. Birth weight was classified on the basis of sex and gestational age specific percentiles. The relationship between birth weight percentile and the risk of stillbirth (all causes except congenital anomaly) was assessed referent to birth weight percentiles in the range 20–80 th . The risk (odds ratio [95% CI] P) of stillbirth was increased with birth weight between the 1 st –3 rd percentile (OR = 8.2 [CI:6.8–9.9] P < 0.001), 4 th –10 th percentile (OR = 3.5 [CI:2.8–4.0] P < 0.001) and the 11 th –20 th percentile (OR = 1. 8 [CI:1.4–2.2] P < 0.001). The risk of stillbirth was also increasing among the largest infants: 98 th –100 th percentile (OR = 2.3 [CI:1.7–3.1] P < 0.001). The attributable fraction for stillbirth associated with these birth weight categories was 33% (95% CI: 28 to 37%). The associations were minimally affected by adjusting for maternal characteristics, including smoking. Conclusion: Approximately one third of all term stillbirths are associated with growth abnormality. These data indicate that population screening for growth abnormality could identify babies at increased risk of term stillbirth.